Model Logistic Regression Dalam Penentuan Kebijakan Dividen Perusahaan Di Indonesia - Agung Satmoko; - Sudarman (Conference In Business, Accounting, And Management (CBAM), 2012)
This paper investagates dividend policy decision in Indonesian Stock Exchange (IDX) through studying non-financial firms. Panel data were obtained from 1490 non-financial firms over the five year period from 2006 to 2010, where 310 firms pay dividend and 1180 firms were not. Logistic regression model were used to test the six research hypotheses. The result revealed that size of firms, debt equity ratio, and return on equity increases the probability of paying dividends, whereas the public ownership decreases the probability of paying dividends. Two variables, free cash flow and growth of sales insignificantly affect to the probability of paying dividends. Overall, research findings that companies list on Indonesian Stock Exchange (IDX) paid dividends to reduce agency conflict and enhance their companies reputation.Keywords: Dividend payout decision, Non-financial firms, Panel data, Logisticregression model.